VD_FINDINFO HC / 2024 / 101 vom 6. März 2024 - VD Tribunal cantonal (2024)
DROIT DU TRAVAIL, CONVENTION COLLECTIVE DE TRAVAIL, FARDEAU DE LA PREUVE, INTERPRÉTATIONSENS GÉNÉRAL, NOTORIÉTÉ | 8 CC, 18 CO, 357 CO